Martensitic transformation and magnetic field induced effects in Ni42Co8Mn39Sn11 metamagnetic shape memory alloy. (1st May 2016) - Lázpita, P.; Sasmaz, M.; Cesari, E.; Barandiarán, J.M.; Gutiérrez, J.; Chernenko, V.A.
Abstract: Transformation and multifunctional properties of a polycrystalline Ni42 Co8 Mn39 Sn11 metamagnetic shape memory alloy have been investigated by extensive measurements of thermomagnetization, thermal expansion and thermoresistance under magnetic field. The martensitic transformation (MT) at zero field is near 300 K but changes moderately with field. Magnetization loops at room temperature show metamagnetic behavior and complete field-induced MT below 12 T. A non-linear phase diagram ' transformation temperatures versus field ' has been established. The correlation between the transformation entropy, ΔS, with magnetic field, and temperature span between MT and Curie temperature has been also established. A transformation volume effect of about 0.45% has been estimated at MT. It has been experimentally proved that the metamagnetic effect is at the origin of the giant effects of the studied alloy, such as volume magnetostriction and magnetoresistance, which have practical importance. Graphical abstract: